Pengaruh Alat Peraga Edukatif (APE) terhadap hasil belajar Matematika pada materi pengurangan di kelas I SD Negeri 4 Kikim Selatan - Irna Juanti; Muhammad Juliansyah Putra; Nora Surmilasari (COLLASE (Creative of Learning Students Elementary Education), 2026)
The concept of subtraction is an important part of mathematics learning at the elementary school level. This study was conducted to analyze “the effect of using educational teaching aids on the mathematics learning outcomes of first-grade students on the subject of subtraction at SD Negeri 4 Kikim Selatan.” The research approach used was a quasi-experiment with a posttest-only control group design. The research subjects included all students at SD Negeri 4 Kikim Selatan, with samples taken from two classes, namely class I.A as the comparison group consisting of 21 students and class I.B as the treatment group consisting of 22 students. Data collection techniques involved observation, testing, and documentation studies. The test instrument consisted of 10 essay questions, of which 7 were deemed valid and 3 did not meet the criteria after undergoing a validity test. From the valid questions, 5 were selected for use as the final test. The results of the analysis showed that the average score of students in the treatment class was 83.18, while the control class obtained an average of 55.00. These findings indicate that “the use of educational teaching aids contributes positively to mathematics learning outcomes in subtraction material in class I of SD Negeri 4 Kikim Selatan.”